2014
DOI: 10.1063/1.4884820
|View full text |Cite
|
Sign up to set email alerts
|

Understanding chemical reactions of CO2 and its isoelectronic molecules with 1-butyl-3-methylimidazolium acetate by changing the nature of the cation: The case of CS2 in 1-butyl-1-methylpyrrolidinium acetate studied by NMR spectroscopy and density functional theory calculations

Abstract: NMR spectroscopy ( 1 H, 13 C, 15 N) shows that carbon disulfide reacts spontaneously with 1-butyl-1-methylpyrrolidinium acetate ([BmPyrro][Ac]) in the liquid phase. It is found that the acetate anions play an important role in conditioning chemical reactions with CS 2 leading, via coupled complex reactions, to the degradation of this molecule to form thioacetate anion (CH 3 COS − ), CO 2 , OCS, and trithiocarbonate (CS 3 2− ). In marked contrast, the cation does not lead to the formation of any adducts allowin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 47 publications
1
26
0
Order By: Relevance
“…However, as shown in Figure 4, a product formed from the [BMIM] + cation was observed by 1 H NMR. In particular, the analysis of the post electrolysis solution showed both distinct peaks for the starting [BMIM] + cation as well as peaks corresponding to the zwitterionic [BMIM]-CO 2 adduct, as characterized by the diagnostic signals at 7.16 ppm in the 1 H NMR spectra [26][27][28]. The structure of the [BMIM]-CO 2 adduct is shown in Figure 5.…”
Section: Catalyst Activitymentioning
confidence: 98%
“…However, as shown in Figure 4, a product formed from the [BMIM] + cation was observed by 1 H NMR. In particular, the analysis of the post electrolysis solution showed both distinct peaks for the starting [BMIM] + cation as well as peaks corresponding to the zwitterionic [BMIM]-CO 2 adduct, as characterized by the diagnostic signals at 7.16 ppm in the 1 H NMR spectra [26][27][28]. The structure of the [BMIM]-CO 2 adduct is shown in Figure 5.…”
Section: Catalyst Activitymentioning
confidence: 98%
“…The reason was that CS2 can react spontaneously with BmimOAc in the liquid phase to form a stable inner-salt compound 1-butyl-3methylimidazolium-2-thiocarboxylate (Bmim + -COS − ) which was got by chromatography on silica gel and structurally characterized by NMR spectra (see Supporting Information). Danten and coworkers 33,34 have reported the same result, and in their studies on chemical reactions of CS2 with ionic liquids, they confirmed that CS2 can undergo degradation to form such compounds. Gao, Mu and coworkers 35 also have summarized some reactions of imidazolium-based ionic liquid with inorganic electrophiles (such as CO2, CS2 and OCS) under alkaline conditions.…”
Section: Reaction Of 2-(phenylamino) Ethanol With Cs2mentioning
confidence: 63%
“…6 completely agreed with the 1 H NMR and 13 C NMR spectra of BmmimCOS. In addition, Danten and coworkers 34,35 also have reported that CS2 can react spontaneously with acetate anion of ionic liquid 1-butyl-1-methylpyrrolidinium acetate ([BmPyrro][OAc]) in the liquid phase. All of the results indicated that the acetate anion of BmmimOAc could react spontaneously with CS2 to form CH3COS − anion.…”
Section: Reaction Mechanism Studiesmentioning
confidence: 99%
“…Acetate‐based ILs are known to play an important role in conditioning chemical reactions with CO 2 with reaction products with low viscosity, compared to most chemisorption solvents . Although most of the work focus on the imidazolium cation, with the sorption mechanism well described and accepted,, Shi et al have shown that for the tetrabutylphosphonium acetate IL the anion controls the large CO 2 solubility by chemisorption, with the cation contributing mostly for the physisorption regime.…”
Section: Resultsmentioning
confidence: 99%